Labor Market Conditions and Social Insurance in China - Johanna Rickne (Research Institute of Industrial Economics (IFN), 2012)
Fifteen years after the introduction of highly ambitious social insurance programs for urban Chinese workers, a large number of them remain un-insured. This paper examines the relationship between labor market conditions and social insurance participation among industrial firms in the pre-crisis years of 20002007. I find that increased labor tightness over this period was a quantitatively important driver of participation. Comparing different segments of the labor market, stronger response to tightness is found in sectors with the largest shares of un-insured: private firms, those with a larger share of low-educated workers, and those without labor unions. Increased tightness in the years ahead can therefore be expected to aid policy makers in social insurance implementation and in combating insurance inequality.
Keywords: D21; J64; J65; 330; Social insurance; Employer participation; Labor market tightness; Peoples Republic of China